Pengaruh CAR, FDR, NPF, DPK dan BOPO terhadap ROA di BTN Syariah Periode 2017-2021 - Alipia Nurjanah; Widya Sari; Lenny Yanthiani; Nano Suyatna (Ma'soem University, 2023)
Based on the observation that the background of this research is the fluctuation of CAR, FDR, NPF, TPF and BOPO, causing the ROA to fluctuate at the bank. This study aims to determine how the effect of CAR, FDR, NPF, DPK and BOPO on ROA either partially or simultaneously at the Islamic State Savings Bank. The object of research in this report uses the Associative Quantitative method with the type of data using secondary data in the form of a quarterly report of the Islamic State Savings Bank for the 2017-2021 Period. The population is all quarterly financial reports of the Islamic State Savings Bank. The sample studied is the Islamic State Savings Bank which is determined through the Purposive Sampling technique. The results of this study indicate that there is no significant and negative effect between CAR on ROA at BTN Syariah by 0.54% with the results of the t test where the value of tcount < ttable (0.313 < 1.753), has no significant effect between FDR on ROA at BTN Syariah and negative direction of 1.12% with a value of tcount < ttable (0.451 < 1.753), there is a significant effect between NPF on ROA at BTN Syariah by 37.4% with the result of the value of tcount < ttable (3.279 > 1.753), there is a significant effect There is a significant difference between DPK to ROA at BTN Syariah by 34.2% with a value of tcount < ttable (4.561 > 1.753), and there is no significant effect between BOPO and ROA at BTN Syariah by 40% with the result of tcount < ttable (0.148 < 1.753). And simultaneously there is no influence between CAR, FDR, NPF, DPK dan BOPO on ROA at BTN Syariah of 24.8% with the result of fcount < ftable (0.92 < 2.96).